The Role of Type 2 Diabetes for the Development of Pathogen-Associated Cancers in the Face of the HIV/AIDS Epidemic - Blumenthal, Melissa J.; Ujma, Sylvia; Katz, Arieh A.; Schäfer, Georgia (Frontiers in Microbiology, 2017)
The contribution of HIV to the development of pathogen-associated cancers has long been recognised, as has the contribution of type 2 diabetes for the development of several types of cancer. While HIV/AIDS-associated immunosuppression reduces immunosurveillance and indirectly contributes favourably to cancerogenesis, diabetes directly increases cancer development due to chronic low-grade inflammation, dysregulated glucose metabolism, hyperactivation of insulin-responsive pathways, and anti-apoptotic signalling. Pathogen-associated cancers contribute significantly to the cancer burden particularly in low- and middle- income countries. In those countries, the incidence of type 2 diabetes has increased alarmingly over the last decades, in part due to rapid changes in diet, lifestyle and urbanisation. It is likely that the HIV/AIDS epidemic and the steadily increasing rate of type 2 diabetes display synergistic effects on oncogenesis. Although this possible link has not been extensively investigated, it might become more important in the years to come not least due to the stimulating effects of antiretroviral therapy on the development of type 2 diabetes. This review provides an overview of the current understanding of pathogen- and diabetes- associated cancers with focus on geographical regions additionally burdened by the HIV/AIDS epidemic. As both HIV and carcinogenic infections as well as the onset of type 2 diabetes involve environmental factors that can be avoided to a certain extent, this review will support the hypothesis that certain malignancies are potentially preventable. Deploying effective infection control strategies together with educational policies on diet and lifestyle may in the long term reduce the burden of preventable cancers which is of particular relevance in low-resource settings.